2020
DOI: 10.1136/bmjsem-2019-000638
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative analysis of head and body impacts in American 7v7 non-tackle football

Abstract: ObjectivesNon-tackle American football is growing in popularity, and it has been proposed as a safer alternative for young athletes interested in American football. Little is known about the nature of head contact in the sport, which is necessary to inform the extent to which protective headgear is warranted. The objective of this study was to identify the location, types and frequency of head and body contacts in competitive 7v7 non-tackle American football.MethodsVideo analysis was used to document the type,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…These findings agree with a study of head contact in organized youth 7v7 football that found that head-to-body contact and head-to-ground contact were the most common sources of head contact and that head-to-head contact was infrequent. 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings agree with a study of head contact in organized youth 7v7 football that found that head-to-body contact and head-to-ground contact were the most common sources of head contact and that head-to-head contact was infrequent. 11…”
Section: Discussionmentioning
confidence: 99%
“…These findings agree with a study of head contact in organized youth 7v7 football that found that head-tobody contact and head-to-ground contact were the most common sources of head contact and that head-to-head contact was infrequent. 11 Interestingly, several non-tackle football injuries were classified as being caused by a vertical object adjacent to the field, such as a brick wall, metal pole, fence, bleacher, or door. Likewise, several injuries referenced hard or manmade ground, including asphalt, concrete, and gym flooring.…”
Section: Primary Diagnosismentioning
confidence: 99%
“…Technological advances in 3D motion capture technology offer the potential for in-game rugby-style tackle technique to be assessed in future research. Model-based image matching is one such emerging technology that uses multiple 2D video camera views and applies a multibody skeletal model to estimate ingame 3D player kinematics [51] or 3D head velocity Reference [22] reported data as medians and upper and lower quartiles [23]; reported as absolute median (25% and 95% confidence interval) [25]; reported data as mean ± SD/SEM or as a mean and an effect size [26]; reported data as mean ± SD [27]; reported data as mean (95% confidence interval) or as r [28]; reported data as either mean (95% confidence interval) or odds ratio (95% confidence interval) or as a mean during a tackle in rugby union [52] and American football [53]. This manual process also takes 60 h to complete a single case study [54].…”
Section: Theme Three-3d Data Collectionmentioning
confidence: 99%
“…Markerless image processing technology to estimate 3D joint angles is valid [51] but not 3D head velocity [54]. It is recommended that due to the low sampling rate of the broadcast video of 100 Hz [54] or game video footage of 25 Hz in rugby union [52] or 60 or 120 Hz in American football [53], neither head velocity nor acceleration should be calculated from broadcast video as its low sampling rate violates Nyquist sampling theorem based on spectral analysis. An alternative technology measuring head acceleration is wearable sensors such as instrument mouthguards [55].…”
Section: Theme Three-3d Data Collectionmentioning
confidence: 99%
“…The few studies that have utilized video as a tool (in combination with sensor data) to examine youth football helmet impacts have primarily focused on high-magnitude impacts (≥ 40g) and used a single-camera system to view the play on the field, limiting the data that can be obtained (Alois et al, 2019;Campolettano et al, 2017;Le et al, 2021). Jadischke et al (2020) developed a novel approach for collecting high-quality video data that used multiple stationary action cameras to analyze head and body impacts in non-tackle American 7v7 football games for youth and varsity-aged players. This approach circumvents common issues of single-camera video analysis, mimicking professional sport by providing multiple views of the field which offers advantages such as: 1) differing camera angles for more detailed characterization of impact cases; 2) a reduced likelihood of excluding cases of interest because of view obstructions (e.g., other players, referees, etc.…”
mentioning
confidence: 99%